Knowledge, Attitude, and Practices (KAP) Regarding Meat Safety and Sanitation among Carcass Handlers Operating and Assessment of Bacteriological Quality of Meat Contact Surfaces at the Marrakech Slaughterhouse, Morocco - Mohammed Amine Bahir; Ikram Errachidi; Mouhssine Hemlali; Bouchaib Sarhane; Asmae Tantane; Alami Mohammed; Bouchra Belkadi; Abdelkarim Filali-Maltouf (International Journal of Food Science)
According to the Moroccan Court of Auditors, the meats are prepared in slaughterhouses that do not meet the basic conditions required by Moroccan standards. This survey is being conducted to assess the knowledge, attitudes, and practices of handlers regarding the salubrity and hygiene of meat and to evaluate the bacteriological load of work surfaces in a slaughterhouse located in the Marrakech region. A total of 100 people working at the slaughterhouse participated in the study. The average values concerning the attitude and practice of the carcass handlers were, respectively, very satisfactory (65.7%) and acceptable (53.44%), while the average value of knowledge was generally low (39%). Bacterial load was assessed by the serial dilution method using the standard procedure. Seventy samples were taken from the hands of manipulators, knives, clothes, hooks, door handles, floor, and walls over an area of between 20 and 100 cm2. The total number of aerobic mesophiles (TAVCs), Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Salmonella spp was determined for each sample. Escherichia coli was the predominant isolate (42%), while Salmonella spp and Pseudomonas aeruginosa were the least bacterial isolates with 16% and 14%, respectively. Walls and knives were the most contaminated by E. coli at 90%. This survey reveals the importance of developing formal training for all slaughterhouse handlers regarding meat hygiene and safety during carcass processing to develop their knowledge and practices. Bacteriological results indicate a need to improve the available slaughter facilities and develop an appropriate slaughter process strategy to minimize the risk of carcass contamination.